Administration of Buddhist University for ASEAN Community - Phramethavinairos (Sutep Buddhacanya); Sirithrungsri, Pinsuda; Thongkhao, Kla (Academic MCU Buriram Journal, 2019)
Thailand is faced with rapid change and high competition in cases of economics, social, politics, governing and technology for participation competency in ASEAN community and world community especially under changing surrounding of globalization which are changing as rapidly and high complexity those are affected to Thai University which are faced a lot of problems and crisis level both in quality and effectively all are fruited from variety of weakness which are effected together as a chain of problem in terms of administrative structure, personal administration, academic administration, budget administration and general administration, therefore the two Sangha Universities; Mahamakut Buddhist University and Mahachulalongkornrajavidyalaya need to stand by for facing off changing situation of globalization current and going to information technology age of the world society throughout participation of ASEAN community with adaptation of vision in administration of Sangha Universities as universal along with changing and competition competency. This abstract has made a body of knowledge from literature review on concept of administration, ASEAN declaration of education, and education of Sangha Universities for presentation of administration of Sangha Universities for supporting of ASEAN community.